A review of the F. serena-subgroup of Fannia Robineau-Desvoidy (Diptera: Fanniidae), with the description of two new species from China - Wang, Ming-Fu; Zhang, Dong; Xue, Wan-Qi (Zootaxa, 2006)
The Fannia serena-subgroup belongs to the Fannia serena-group Chillcott. This paper outlines early studies on the F. serena-subgroup and F. serena-group. The F. serena-group is redefined and a key is given to its four subgroups: serena-subgroup Chillcott, rondanii-subgroup Chillcott, sociella- subgroup Chillcott, and mollissima-subgroup Pont. Two new species, Fannia diploura Wang, Xue & Zhang sp. nov. and Fannia setifemorata Wang, Xue & Zhang sp. nov., are described from China. The eleven known Chinese species of the F. serena-subgroup are reviewed and keyed.